FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR SEBAGAI PROFESI AKUNTAN PUBLIK BAGI MAHASISWA AKUNTANSI - Alvin Juliansah; Rossje V Suryaputri (Jurnal Akuntansi Trisakti, 2016)
The purpose of this study is to analyze the factors that influence the selection of career as a profession of public accountant. Factors measured in this study with variable intrinsic value of work, financial rewards, labor market considerations, social values, work environment and personality. Data collected through questionnaires to accounting students at Trisakti Universities in West Jakarta. Samples used in this study are 90 respondents. This study has two variables: independept variable and dependent variable, where the independent variables are intrinsic value of work, financial rewards, labor market considerations,social values, work environment, and personality. And the dependent variable is career selection as public accountant profession. Analysis of the data in this study using multiple regression analysis with the SPSS2016. The results of this analysis showed that the variables intrinsic value of work, financial rewards, work environment,, social values, consideration of the labor market, and personality significant effect on career choice became public accountant by accounting students